Incretin-based therapy and risk of cholangiocarcinoma: a nested case–control study in a population of subjects with type 2 diabetes - Giorda, Carlo B.; Picariello, Roberta; Tartaglino, Barbara; Nada, Elisa; Costa, Giuseppe; Gnavi, Roberto (Acta diabetologica, 2020)
Background and aims One cohort and several basic science studies have raised suspicion about an association between incretin therapies and cholangiocarcinoma. Our aim was to verify the occurrence of CC in relation to incretin-based medication use versus any antidiabetic treatment in an unselected population of diabetic patients. Methods A population-based matched case–control study was conducted using administrative data from the Region of Piedmont (4,400,000 inhabitants), Italy. From a database of 312,323 patients treated with antidiabetic drugs, we identified 744 cases hospitalized for cholangiocarcinoma from 2010 to 2016 and 2976 controls matched for gender, age and initiation of antidiabetic therapy; cases and controls were compared for exposure to incretin-based medications. All analyses were adjusted for risk factors for CC, as ascertained by hospital discharge records. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated by fitting a conditional logistic model. Results The mean age of the sampled population (cases and controls, 75 years) was very high, with no gender prevalence. Five per cent was treated with incretin-based medications. After adjusting for possible confounders, we found no increased risk of cholangiocarcinoma associated with the use of either DPP4i (OR 0.98, 95% CI 0.75–1.29: p = 0.89) or GLP-1-RA (OR 1.09, 95% CI 0.63–1.89; p = 0.76) in the 24 months before hospital admission. Neither the duration of the therapy nor the dose modified the risk of cholangiocarcinoma. Conclusions Our findings suggest that, in an unselected population, the use of both classes of incretin-based medications is not associated with an increased risk of cholangiocarcinoma.